Mindfulness Breathing Reduce Stress in Final Student - Tasya Salsabila Shafaa'; Retno Twistiandayani; Natalia Christin Tiara Revita (Health Gate, 2026)
Background: Stress is a mental health problem often experienced by final year students due to academic demands, thesis completion, and future uncertainty. One non-pharmacological intervention that can be used to reduce stress is mindfulness breathing. Objective: The aim is to analyze the effect of mindfulness breathing on the stress levels of final year students at Semen Indonesia International University (UISI). Methods: The study used a quasi-experimental pretest-posttest design with a control group. The sample consisted of 86 students divided into an intervention group and a control group of 43 respondents each. Stress levels were measured using the Depression Anxiety Stress Scales (DASS-42) instrument. The intervention group was given mindfulness breathing exercises for 4 weeks with a duration of 10 minutes per day. Results: The results showed that before the intervention, most respondents experienced severe stress (99%). After the intervention, stress levels decreased to moderate (69%), mild (30%), and normal (1%) categories. The results of statistical tests showed a p value = 0.000 (p < 0.05). Conclusion: There is a significant effect of mindfulness breathing on reducing stress levels of final year students. This intervention can be an effective alternative in helping students manage academic stress.